Peran Pengawasan Dalam Meningkatkan Disiplin Kerja Pegawai Aparatur Sipil Negara Pada Kementerian Agama - Yusuf, Abdul Rahman (CV. Dalle’ Deceng Abeeayla, 2024)
This study was conducted with the aim of finding out the role of supervision in improving the discipline of civil servants at the Ministry of Religion of Bone Bolango Regency. This study uses a qualitative approach and descriptive method. The results of the study indicate that: Supervision plays a major role in shaping the discipline of civil servants at the Ministry of Religion of Bone Bolango Regency, and this supervision can only run if the leadership at the Ministry of Religion of Bone Bolango Regency carries out their duties as actors in supervision; That based on the data, the discipline of civil servants at the Ministry of Religion office is still not optimal, not because there is no supervision, but because the leadership does not understand theoretically or practically the technical aspects of supervision, resulting in less than optimal supervision at the Ministry of Religion of Bone Bolango Regency; That supervision is not only a system or rule that is the basis for implementation in an agency but is a fundamental principle in managing an institution such as the Ministry of Religion of Bone Bolango Regency, this means that supervision plays an important role in improving the discipline of the State Civil Apparatus, so that increasing human resources in the leadership is the keyword in realizing supervision in order to improve the discipline of the State Civil Apparatus.